Perceptions of caregivers regarding factors contributing to poor academic results of children living in alternative care: a case of selected Child and Youth Care Centres (CYCCs) in Ekurhuleni - Ndhlovu, B (My University, 2021)
Globally, children are placed in alternative care for different reasons such as neglect, abuse, and orphan-hood. It is recognized that while these children are living in alternative care, they perform poorly at school and the reasons for their poor academic results are uncertain. While much research, within the South African context, has precisely focused on the wellbeing and the impact of HIV and AIDS on children living in alternative care, less focus has been paid on their education and the factors that contribute to the poor academic results. Some children in alternative care often get poor results in school, which forces them to remain in the same grades without progression. Within the South African context, researchers have not paid much attention to the issue of poor academic results shown by some children in alternative care. This lack of literature and research within the South African context is of great concern as the issue of alternative care seems to be far from over. Therefore, it is because of this lack of research and gap in the literature that this study aimed at exploring the perceptions of caregivers regarding the factors contributing to poor academic results of children living in alternative care, with a specific focus on Child and Youth Care Centres (CYCCs) in Ekurhuleni. The study utilized a qualitative research approach, with a case study used as a research design. Purposive sampling was used to select 15 caregivers to participate in the study, together with two social workers who were key informants. All participants were recruited from the CYCCs in Ekurhuleni. A semi-structured interview guide was used as a research tool, with face-to-face interviews used as a method of data collection. Data collected was analyzed thematically, using thematic analysis. The findings of the study revealed that children’s previous background, placement into CYCCs, together with the change of schools were amongst the factors that contributed to their poor academic results. Recommendations are made concerning future research
A dissertation submitted to the Department of Social Work, School of Human and Community Development, Faculty of Humanities, University of the Witwatersrand in partial fulfilment of the requirements for the Master of Arts (in Social Work), 2021